"NaClO2-Sea Water" Wet Denitrification Technology Using NOx Treatment Technology in the Desulfurization and Denitrification of Ship Exhaust Gas. Issue 1 (February 2020) - Chen, Peng
Abstract: To minimize the emission pollution of nitrogen oxides (NOx) in marine diesel engine exhaust, based on the existing NOx treatment technology, the "NaClO2 -sea water" wet denitrification technology was further proposed. The denitrification performance of NaClO2 solution in seawater and NaClO2 solution in fresh water was analyzed by self-designed and built experimental platform. Moreover, the effects of the temperature of the absorption solution, the initial concentration of NaClO2 and the concentration of NO in diesel exhaust gas on the denitrification performance of NaClO2 sea water solution were studied. The experimental results showed that the denitrification rate of NaClO2 solution with seawater as solvent was slightly lower than that of NaClO2 solution with fresh water, but the denitrification duration of seawater solution had obvious advantages over that of fresh water solution. In addition, by increasing the temperature of the absorption solution and the initial concentration of NaClO2 and decreasing the concentration of NO, the denitrification rate of NaClO2 sea water solution was increased. Whereas, if the temperature exceeded a certain limit, the continuous denitrification time of the solution would be decreased. Therefore, "NaClO2 -sea water" wet denitrification technology has the advantages of cheap raw materials and long continuous denitrification time. High denitrification efficiency can be achieved by optimizing reaction conditions, so it can be used for denitrification of marine diesel engine exhaust gas.